"Mind the Gap": Hi-C Technology Boosts Contiguity of the Globe Artichoke Genome in Low-Recombination Regions. Issue 10 (1st October 2020) - Acquadro, Alberto; Portis, Ezio; Valentino, Danila; Barchi, Lorenzo; Lanteri, Sergio
Abstract: Globe artichoke ( Cynara cardunculus var. scolymus ; 2n2x=34) is cropped largely in the Mediterranean region, being Italy the leading world producer; however, over time, its cultivation has spread to the Americas and China. In 2016, we released the first (v1.0) globe artichoke genome sequence (http://www.artichokegenome.unito.it/ ). Its assembly was generated using ∼133-fold Illumina sequencing data, covering 725 of the 1, 084 Mb genome, of which 526 Mb (73%) were anchored to 17 chromosomal pseudomolecules. Based on v1.0 sequencing data, we generated a new genome assembly (v2.0), obtained from a Hi-C (Dovetail) genomic library, and which improves the scaffold N50 from 126 kb to 44.8 Mb (∼356-fold increase) and N90 from 29 kb to 17.8 Mb (∼685-fold increase). While the L90 of the v1.0 sequence included 6, 123 scaffolds, the new v2.0 just 15 super-scaffolds, a number close to the haploid chromosome number of the species. The newly generated super-scaffolds were assigned to pseudomolecules using reciprocal blast procedures. The cumulative size of unplaced scaffolds in v2.0 was reduced of 165 Mb, increasing to 94% the anchored genome sequence. The marked improvement is mainly attributable to the ability of the proximity ligation-based approach to deal with both heterochromatic ( e.g. : peri-centromeric) and euchromatic regions during the assembly procedure, which allowed to physically locate low recombination regions. The new high-quality reference genome enhances the taxonomic breadth of the data available for comparative plant genomics and led to a new accurate gene prediction (28, 632 genes), thus promoting the map-based cloning of economically important genes.